Biotransformations of nitriles mediated by in vivo nitrile hydratase of Rhodococcus erythropolis ATCC 4277 heterologously expressed in E. coli - Maraylla I. Moraes; César Iglesias; Iris S. Teixeira; Humberto M.S. Milagre; Sonia Rodríguez Giordano; Cintia D.F. Milagre (Results in Chemistry, 2023)
Nitrile hydratase activity has been reported as an exciting alternative for the industrial production of a variety of compounds overwhelming its chemical counterpart; despite this, until now, a few enzymes have been thoroughly studied. Efficient expression of nitrile hydratase enzymes has been the bottleneck to explore this activity. Here, we report the cloning and expression of Rhodococcus erythropolis ATCC 4277 nitrile hydratase (α- and β-subunits) and the correspondent activator gene. Furthermore, substrate scope with whole cells of recombinant E. coli demonstrates that this Fe-type NHase could hydrate a wide range of aliphatic and aromatic nitrile with high conversion rates and moderate enantiomeric excess.